2013
DOI: 10.1111/ejh.12234
|View full text |Cite
|
Sign up to set email alerts
|

Poor responses to tyrosine kinase inhibitors in a child with precursor B‐cell acute lymphoblastic leukemia with SNX2‐ABL1 chimeric transcript

Abstract: In addition to BCR, various rare fusion partners for the ABL1 gene have been reported in leukemia. We have identified the fusion gene SNX2-ABL1 in a pediatric case of acute lymphoblastic leukemia (ALL), which has only once previously been reported in an adult patient. Cytogenetic analysis detected this fusion gene arising from a t(5;9)(q22;q34) translocation. ALL cells carrying a SNX2-ABL1 fusion exhibited a BCR-ABL1+ ALL-like gene expression profile. The patient poorly responded to dasatinib but partially res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…mRNA-seq was performed in 92 patients in the TCCSG cohort and 17 patients in the JACLS cohort (total 109 patients) according to previously described methods. 16 Briefly, the cDNA libraries were loaded on to the cBot (Illumina, Inc., San Diego, CA, USA) for clustering on a flow cell and then sequenced using a HiSeq1000 (Illumina). A paired-end run was performed using the SBS Kit (Illumina).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…mRNA-seq was performed in 92 patients in the TCCSG cohort and 17 patients in the JACLS cohort (total 109 patients) according to previously described methods. 16 Briefly, the cDNA libraries were loaded on to the cBot (Illumina, Inc., San Diego, CA, USA) for clustering on a flow cell and then sequenced using a HiSeq1000 (Illumina). A paired-end run was performed using the SBS Kit (Illumina).…”
Section: Methodsmentioning
confidence: 99%
“…mRT-PCR was used in 264 patients (68 in the TCCSG cohort, 95 in the JACLS cohort, 83 in the CCLSG cohort and 18 in the KYCCSG cohort) to determine the presence of 15 kinase fusions, including ZMIZ1-ABL1 , SNX2-ABL1 , FOXP1-ABL1 , SFPO-ABL1 , EML1-ABL1 , NUP214-ABL1 , RCSD1-ABL1 , ETV6-ABL1 , RANBP2-ABL1 , STRN3-JAK2 , BCR-JAK2 , PAX5-JAK2 , EBF1-PDGFRB , ATF7IP-PDGFRB and P2RY8-CRLF2 . 6 , 16 , 18 The primers used in this study are listed in Supplementary Table S1 . 6 The consort diagram of the genetic analysis is described in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MLPA analysis revealed that 34 of 278 (12·2%) patients harboured the IKZF1 deletion. To identify putative kinase fusion transcripts cooperating with IKZF1 deletion, mRNA sequencing was performed in the 16 patients for whom sufficient RNA was available, as described previously (Masuzawa et al , ). The putative transcripts were validated by reverse transcription polymerase chain reaction (RT‐PCR) and Sanger sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…For the determination of unrevealed genetic alterations causing CRLF2 OE, mRNA‐seq was performed in seven CRLF2 OE patients harboring IKZF1 deletions, where sufficient RNA samples were available, according to previously described methods (Masuzawa et al, ).…”
Section: Methodsmentioning
confidence: 99%